Are matching funds for smallholder irrigation money well spent?. (April 2018) - Mullally, Conner; Chakravarty, Shourish
Highlights: We study the Rural Business Development program for Nicaraguan plantain producers. The program subsidized inputs, extension, and irrigation for plantain producers. We evaluate the program using machine learning and doubly robust estimation methods. The program had large positive impacts on revenue, production, and yield. We find no program impacts on household expenditure. Abstract: Groundwater irrigation can dramatically affect agricultural production and productivity. Despite its potential as an agricultural development tool, little credible evidence exists for the impacts of groundwater development on smallholder agriculture. We add to the evidence on the benefits of irrigation investments for small producers by evaluating the Rural Business Development (RBD) program of the Millennium Challenge Corporation in Nicaragua for small plantain producers. The RBD program offered matching funds covering up to 30% of the cost of two years of inputs, extension services, and diesel-powered micro-sprinkler irrigation for individual farms. In order to estimate the average impact of the RBD program on its beneficiaries, we combine model selection via the LASSO with doubly robust treatment effect estimation as applied to two years of panel data for 146 producers. We find that the program had substantial impacts on plantain revenue and production, while achieving nearly complete irrigation coverage of plantain land among beneficiaries. We find no discernible impact on household expenditure.